A prospective, multicenter trial of a long-term bioabsorbable mesh with Sepra technology in cohort of challenging laparoscopic ventral or incisional hernia repairs (ATLAS trial). (January 2022) - Hope, William W.; El-Ghazzawy, Adel G.; Winterstein, Brad A.; Blatnik, Jeffrey A.; Davis, S. Scott; Greenberg, Jacob A.; Sanchez, Noel C.; Pauli, Eric M.; Tseng, Daniel M.; LeBlanc, Karl A.; Roberts, Kurt E.; Bower, Curtis E.; et al.
Abstract: Background: This prospective, multicenter, single-arm, open-label study evaluated P4HB-ST mesh in laparoscopic ventral or incisional hernia repair (LVIHR) in patients with Class I (clean) wounds at high risk for Surgical Site Occurrence (SSO). Methods: Primary endpoint was SSO requiring intervention <45 days. Secondary endpoints included: surgical procedure time, length of stay, SSO >45 days, hernia recurrence, device-related adverse events, reoperation, and Quality of Life at 1, 3, 6, 12, 18, and 24-months. Results: 120 patients (52.5% male), mean age of 55.0 ± 14.9 years, and BMI of 33.2 ± 4.5 kg/m 2 received P4HB-ST mesh. Patient-reported comorbid conditions included: obesity (86.7%), active smoker (45.0%), COPD (5.0%), diabetes (16.7%), immunosuppression (2.5%), coronary artery disease (7.5%), chronic corticosteroid use (2.5%), hypoalbuminemia (0.8%), advanced age (10.0%), and renal insufficiency (0.8%). Hernia types were primary ventral (44.2%), primary incisional (37.5%), recurrent ventral (5.8%), and recurrent incisional (12.5%). Patients underwent LVIHR in laparoscopic (55.8%) or robotic-assisted cases (44.2%), mean defect size 15.7 ± 28.3 cm 2, mean procedure time 85.9 ± 43.0 min, and mean length of stay 1.0 ± 1.4 days. There were no SSOs requiring intervention beyond 45 days, n = 38 (31.7%) recurrences, n = 22 (18.3%) reoperations, and n = 2 (1.7%) device-related adverse events (excluding recurrence). Conclusion: P4HB-ST mesh demonstrated low rates of SSO and device-related complications, with improved quality of life scores, and reoperation rate comparable to other published studies. Recurrence rate was higher than expected at 31.7%. However, when analyzed by hernia defect size, recurrence was disproportionately high in defects ≥7.1 cm 2 (43.3%) compared to defects <7.1 cm 2 (18.6%). Thus, in LVIHR, P4HB-ST may be better suited for small defects. Caution is warranted when utilizing P4HB-ST in laparoscopic IPOM repair of larger defects until additional studies can further investigate outcomes. Highlights: Prospective, multicenter, single-arm, open-label study of P4HB-ST mesh LVIHR. Class I (clean) wounds at high risk for Surgical Site Occurrence (SSO). P4HB-ST exhibited few SSO and device-related complications, and improved QoL. Recurrence rate was higher than expected, especially in large defects (≥7.1 cm 2 ). In LVIHR, P4HB-ST may be better suited for small defects (<7.1 cm 2 ).